由题, x 的取值可能为0、1、2、3、4、5、6
分别模7可得1,4,6,6,3,3,5
当 x = 0 , y 2 = 1 mod 7 , 故 y = 1 或 y = 7 当 x = 1 , y 2 = 4 mod 7 , 故 y = 2 或 y = 5 当x=0,y^2=1\text{ mod 7 },故y=1或y=7\\ 当x=1,y^2=4\text{ mod 7 },故y=2或y=5 当x=0,y2=1 mod 7 ,故y=1或y=7当x=1,y2=4 mod 7 ,故y=2或y=5
故 E 7 ( 2 , 1 ) E_7(2,1) E7(2,1)的所有点为: ( 0 , 1 ) ( 0 , 6 ) ( 1 , 2 ) ( 1 , 5 ) (0,1)(0,6)(1,2)(1,5) (0,1)(0,6)(1,2)(1,5)
P = ( 3 , 5 ) , − P = ( 3 , − 5 ) 又 − 5 ( m o d 7 ) = 2 , 故 − P = ( 3 , 2 ) Q = ( 2 , 5 ) , − Q = ( 2 , − 5 ) 又 − 5 ( m o d 7 ) = 2 , 故 − P = ( 2 , 2 ) R = ( 5 , 0 ) , − Q = ( 5 , 0 ) P = (3,5),-P=(3,-5)\\ 又-5(mod \text{ 7}) =2,故-P=(3,2)\\ \\ Q = (2,5),-Q=(2,-5)\\ 又-5(mod \text{ 7}) =2,故-P=(2,2)\\ \\ R = (5,0),-Q=(5,0) P=(3,5),−P=(3,−5)又−5(mod 7)=2,故−P=(3,2)Q=(2,5),−Q=(2,−5)又−5(mod 7)=2,故−P=(2,2)R=(5,0),−Q=(5,0)
由题,p=11,a=1,b=7
由 X R = ( λ 2 − X P − X Q ) m o d p , Y R = ( λ ( X P − X R ) − Y P ) m o d p X_R=(\lambda^2-X_P-X_Q)mod\text{ p},Y_R=(\lambda(X_P-X_R)-Y_P)mod\text{ p} XR=(λ2−XP−XQ)mod p,YR=(λ(XP−XR)−YP)mod p